PEMANFAATAN SISTEM INFORMASI GEOGRAFIS DALAM PENGEMBANGAN SMART TOURISM BATAM PADA LOCATION BASED SERVICE BERBASIS ANDROID - I Made, Sondra Wijaya; Silitonga, Frangky (PPM Sdirjianbang Akademi Militer, 2023)
Tourism has become an important sector in economic development and regional development in Batam, Riau Archipelago. In order to take advantage of the maritime tourism potential of the City of Batam, the use of Geographic Information Systems (GIS) is crucial to facilitate the development and management of tourism destinations. This study aims to investigate the use of GIS in developing tourism in Batam. This research method involves literature study and analysis of secondary data collected from various reliable sources. The collected data were analyzed descriptively to identify tourism potential in Batam and evaluate the use of GIS in tourism development. The results of this study indicate that the use of GIS has made a significant contribution to the development of marine tourism in Batam. GIS enables the collection, integration and visualization of adequate geographic data, which enables better decision-making in infrastructure development, determination of tourist locations and mapping of natural resources. In addition, GIS also increases the efficiency of tourism management, including management of tourist information, environmental monitoring and security oversight. However, this study also identified several challenges faced in using GIS in developing tourism in Batam. These challenges include a lack of awareness and understanding of the benefits of GIS, limited human resources skilled in using GIS technology, as well as infrastructure and connectivity issues. To optimize the use of GIS in developing tourism in Batam, this study recommends efforts to increase awareness and training for stakeholders regarding the implementation of GIS. Close collaboration between the government, tourism managers and the local community is also important to create a conducive environment for the development of sustainable marine tourism